Influence of Natural, Climatic, and Industrial Factors on Air and Water Quality in The Kemerovo Region (Kuzbass, Russia) - Maria Osintseva; Ivan Ishutin (Qubahan Academic Journal)
Geographical and climatic features of the Kemerovo region (Kuzbass, Russia) determined the modern geological and geomorphological structure of the territory, as well as a characteristic pattern in the distribution of mineral deposits. The purpose of this work was to study the geomorphological and hydrological features of the Kemerovo region. Atmospheric circulation, relief, and vegetation are the climate's main factors. The combination of these factors forms the climatic characteristics of the region. Soils in open areas (meadows, hayfields) occupy a small area and have high economic and ecological value. Most of the forest is not affected by economic activities. The exception is disturbances in the territories affected by logging and mining enterprises, which especially affect the air and water quality in the region. All the obtained results of the assessment of the geomorphological and hydrological condition of the Kemerovo region should be used when planning further experiments on the stages of technical and biological reclamation of disturbed lands of mining enterprises to restore vegetation cover and the primary state of soils.